Unstash the Cash! Corporate Governance Reform in Japan - Chie Aoyagi; Giovanni Ganelli (Journal of Banking and Financial Economics)
Japan’s high corporate savings might be holding back growth, by preventing a more effi cient use of resources. Small and medium enterprises (SMEs) have been the main contributors to high corporate cash balances, but more recently larger companies have also increased cash holdings. This paper focuses on the causes and consequences of the current corporate behavior and suggests options for reform. In particular, Japan’s weak corporate governance – as measured by available indexes – might be contributing to high cash holdings. An empirical analysis on a panel of Japanese fi rms confi rms that improving corporate governance would help unlock corporate savings. The main policy implication of the analysis carried out in this paper is that a more ambitious and comprehensive corporate governance reform should be a key component of Japan’s growth strategy. Such a reform would help remove some of the bottlenecks of the legal and corporate governance framework which encourage high corporate cash holdings and prevent a more pro-growth use of resources.